Determination of plasma temperature and electron density of iron in iron slag samples using laser induced breakdown spectroscopy. (August 2016) - Hussain, T.; Gondal, M. A.; Shamraiz, M.
Abstract: Plasma temperature and electron density of iron in iron slag samples taken from a local plant is studied. Optimal experimental conditions were evaluated using Nd: YAG laser at 1064 nm. Some toxic elements were identified and quantitative measurements were also made. Plasma temperature and electron density were estimated using standard equations and well resolved iron spectral lines in the 229.06-358.11 nm region at 10, 20, 30 and 40 mJ laser pulse energy with 4.5 μs delay time. These parameters were found to increase with increase in laser pulse energy. The Boltzmann distribution and experimentally measured line intensities support the assumption that the laser-induced plasma was in local thermal equilibrium. It is worth mentioning that iron and steel sector generates tons of solid waste and residues annually containing variety of contaminants which can be harmful to the environment and therefore knowledge, proper analysis and investigation of such iron slag is important.